Effect of fertigation on growth and yield of summer tomato (Lycopersicon esculentum) using different rates and sources of fertilizers - Prabhakar, M; Hebbar, S S; Nair, A K (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted to study the effect of fertigation on yield of summer tomato (Lycopersicon esculentum Mill. noun. cons). The total seven treatments comprising of varying rates and different sources of fertilizers were applied. Application of 50% of N:P:K fertigation of 70% of the recommended dose gave higher plant height (62.7 cm) and number of branches (10.2). In general treatments receiving the fertigation had taken less number of days for flowering and fruiting over the conventional soil application of fertilizers. All the fertigation treatments recorded higher marketable tomato yield over the conventional soil application of fertilizers to the tune of 10.75 to 20.69%. Among fertigation treatments application of common N: K fertilizers at 50% of recommended dose through fertigation and the other 50% as soil application and water soluble fertilizers at 70% of recommended dosages resulted in higher marketable fruit yields. The highest net income (₹104 420) and B:C ratio (0.88) was obtained with the treatment received 50% of recommended dose of N:K using common fertilizers supplied through fertigation.